The Historicity of Food Habits as Imagined in the Folk Literature of Erstwhile Kalingo: A Study through the Folk Songs of Chati-Ghoda of Odisha and Bitiali of West Bengal - Panda, Sachidananda; Mukherjee, Abhik (Mindscape: A Journal of English & Cultural Studies, 2023)
An effort to get a glimpse of a world-view can be seen through the prisms of rural folk music. They are not only a medium of entertainment for the rural masses, but also a reflection of the untainted rural society that has remained untouched by the humdrum of modernity even today. The rural people live by the age-old practises, beliefs, rituals, and wisdom of traditional knowledge. This paper aims to reproduce the concept of folk music and its typical characteristics, replete with nuances of those pearls of wisdom, that have remained a guiding force for the country people for generations, and how folk music, other than being the prime source of entertainment, is a storehouse of knowledge about the customs, food habits, rituals, and other social behaviours that resonate with the life and living of the populace. This will also highlight some of the extensive citations from the available oral traditions of music.